The Essential Meaning of Self-Actualization via Principalship: A Phenomenological Study - Gökhan Özaslan (Anı Publishing, 2018)
According to Abraham Harold Maslow, self-actualization can be defined as using one's own potential in full. He described it as a higher sort of human need, which must be satisfied to reach healthiness and achieve the full range of desirable personality traits. The aim of this phenomenological study is to reveal the shared meaning of self-actualization in the context of school principalship as derived from the articulated beliefs of a number of public and private school principals. Twelve principals from both public and private schools were interviewed about the meaning of self-actualization as described by literature on the topic. The findings from semi-structured interviews of the participants revealed a consensus that there are five prominent skills which constitute a principal's fully-realized potential: communication, organization, motivation, empathy, and self-improvement. As a consequence of realizing their individual potential, the participants expressed feelings of happiness, peace, and enjoyment in their work, as well as an increase in their self-confidence and self-motivation. However, the participants expressed feelings of a short-term loss of morale and increased unhappiness whenever they failed to realize their individual potential due to impediments encountered in the field. Possible implications for research and practice are also offered.